2022
DOI: 10.3390/a15080280
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends, Enabling Technologies and Application Areas for Big Data

Abstract: The availability of large amounts of data in combination with Big Data analytics has transformed many application domains. In this paper, we provide insights into how the area has developed in the last decade. First, we identify seven major application areas and six groups of important enabling technologies for Big Data applications and systems. Then, using bibliometrics and an extensive literature review of more than 80 papers, we identify the most important research trends in these areas. In addition, our bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…This group has almost a decade of experience of working with Big Data research together with international partners and partners from industry and society. The group has published more than 150 research articles related to Big Data, some of these aimed at identifying trends and research directions [2][19] (more information about one of the large research projects done in the group can be found on https://a.bth.se/bigdata/).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This group has almost a decade of experience of working with Big Data research together with international partners and partners from industry and society. The group has published more than 150 research articles related to Big Data, some of these aimed at identifying trends and research directions [2][19] (more information about one of the large research projects done in the group can be found on https://a.bth.se/bigdata/).…”
Section: Discussionmentioning
confidence: 99%
“…for Big Data research. The group has done similar efforts before, but in that case without the support of a mining program but instead based on interviews with industry experts and senior international researchers in Big Data [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this era of big data, the application of data spans across nearly every aspect of life, bringing more intelligent solutions and innovations to various scenarios and achieving unexpected results. For instance, in the field of telecommunications, these data can facilitate operators in predicting and balancing network load; in the field of energy, meteorologists can predict the production of wind, light, and other renewable energy based on data such as weather and seasons [1]. The abundance of data allows individuals to glean fresh insights and observations that contribute to the advancement of societal infrastructure.…”
Section: Introductionmentioning
confidence: 99%